Synthesis, antibacterial, antifungal and anti-HIV activities of norfloxacin Mannich bases - Pandeya S.N.; Sriram D.; Nath G.; De Clercq E. (My University, 2025)
Mannich bases of norfloxacin were synthesized by reacting them with formaldehyde and several isatin derivatives. Their chemical structures have been confirmed by means of their IR, 1H-NMR data and by elemental analysis. Investigation of in vitro antimicrobial activity of compounds was done by the agar dilution method against 28 pathogenic bacteria, eight pathogenic fungi and anti-HIV activity against replication of HIV-1 (III B) in MT-4 cells. The in vivo antibacterial efficacy of selected derivatives was determined using a mouse infection model. All the synthesized compounds are more active than norfloxacin against the 13 bacteria tested. The compounds are also more active than the standard drug clotrimazole against Histoplasma capsulatum. Two compounds S-8 and S-9 have shown inhibition against HIV-1 (III B) with EC50 values of 11.3 and 13.9 μg/mL, respectively. In the mouse protection test, two compounds S-4 (ED50: 1.25 mg/kg) and S-9 (ED50: 1.62 mg/kg) are more active than norfloxacin (ED50: 6mg/kg). Among the compounds tested, 1- ethyl-6-fluoro-l,4-dihydro-4-oxo- 7[[N4-[5'-bromo-3-(4'-amino-5- trimethoxybenzylpyrimidin-2'-yl]-imino-1'-isatinyl]methyl]N1-piperazinyl]-3- quinoline carboxylicacid (S-9) showed promising activity in all the three tests. (C) 2000 Editions scientifiques et medicales Elsevier SAS.